Effects of chemical hydrolysis operating parameters on the production of antioxidant from fish waste - Wai, A. L. S.; Rohaida, Che Man; Siti Kholijah, Abdul Mudalip; Siti Zubaidah, Ismail; Zatul Iffah, Mohd Arshad; Shalyda, Md Shaarani (IOP Publishing, 2020)
Fish waste is commonly found in the fish market, households and it can be processed into value-added products such as antioxidants. In this study, chemical hydrolysis was selected to produce antioxidants because it was more suitable for industrial scale, shorter time and cheaper compared to enzymatic hydrolysis [1]. However, there was less information on the operating parameters of chemical hydrolysis. Therefore, the objectives of this study were to investigate the effect of types of solvents used, the concentration of HCl, demineralization time and deproteinization time by One Factor in Design Expert on the production of antioxidant from fish waste. In the chemical hydrolysis process, the fish wastes undergo two steps of processes which are demineralization and deproteinization. In this work, demineralization was carried out by 10g of fish waste which was immersed in 0.2 M to 1.0 M of Hydrochloric acid (HCl) for 30 min to 150 min at room temperature and continued stirring at 150 rpm. After washing with distilled water and oven-dried at 60 ℃ for 5 hours, the sample was slowly added into 1.0 M of Sodium Hydroxide (NaOH) for 30 min to 150 min at 60 ℃ and continued stirring at 150 rpm for the deproteinization to occur. These samples were then washed with distilled water and oven-dried at 60 ℃ for 5 hours. DPPH and Total Phenolic Compound (TPC) assays were used to analyze the availability of antioxidant by calculating the percentage of antioxidant activity and Gallic Acid Equivalent, GAE (g/L). The best value of the concentration of HCl, demineralization time and deproteinization time was determined by Analysis of Variance (ANOVA) of Design Expert 7.1.6. The best concentration of HCl used was 0.72 M at 92 min of demineralization, 70 min of deproteinization and ethanol as the suitable solvent used in DPPH and TPC assays.